Overexpression of ANO1/TMEM16A, an arterial Ca2+-activated Cl− channel, contributes to spontaneous hypertension - Wang, Bingxiang; Li, Chunlin; Huai, Ruituo; Qu, Zhiqiang (Journal of molecular and cellular cardiology, 2015)
Calcium-activated chloride channels (CaCCs) have been implicated in hypertension; however, the mechanism underlying their involvement is unknown. The aim of this study was to determine whether the CaCC ANO1 is involved in the pathogenesis of spontaneous hypertension. Arterial ANO1 expression and the effects on blood pressure (BP) of inhibiting ANO1 with an ANO1 inhibitor, T16Ainh-A01, and in vivo RNAi, were examined in spontaneously hypertensive rats (SHRs). Knockdown of ANO1 by siRNA prevented hypertensive development, and attenuation of ANO1 channel activity reduced BP in SHRs. Angiotensin II upregulated ANO1 expression in primary cultures of vascular smooth muscle cells (VSMCs). The protein level and activity of cellular ANO1 positively correlated with VSMC proliferation. Our data indicate an important role of increased ANO1 expression and activity in inducing hypertension in SHRs. It may mediate angiotensin II-dependent vascular remodeling. Our results increase the mechanistic understanding of hypertension and suggest ANO1 as a possible therapeutic target for hypertension. •The calcium-activated chloride channel ANO1 has been implicated in hypertension.•Knockdown of ANO1 prevents hypertension in spontaneously hypertensive rats.•Angiotensin II enhances ANO1 expression via the AT1R-PI3K-Akt pathway.•ANO1 is a potential therapeutic target for spontaneous hypertension.